2018
DOI: 10.1091/mbc.e17-01-0031
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic defects lead to neuronal aneuploidy and apoptosis in frontotemporal lobar degeneration caused by MAPT mutations

Abstract: Mutant Tau (MAPT) can lead to frontotemporal lobar degeneration (FTLD). Previous studies associated MAPT mutations and altered function with aneuploidy and chromosome instability in human lymphocytes and in Drosophila development. Here we examine whether FTLD-causing mutations in human MAPT induce aneuploidy and apoptosis in the mammalian brain. First, aneuploidy was found in brain cells from MAPT mutant transgenic mice expressing FTLD mutant human MAPT. Then brain neurons from mice homozygous or heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
(77 reference statements)
2
33
0
Order By: Relevance
“…Moreover, live cell imaging analyses indicated that multinucleated giant cells resulted from a failure in cell division ( Fig. S2d and Supplementary Movie 4); as reported by others [51], mitotic abnormalities, chromosome mis-segregation, and aneuploidy were observed in transgenic mice expressing the human P301S FTLD-MAPT mutation.…”
Section: Tau Inclusions Accumulate On the Nuclear Envelopesupporting
confidence: 81%
“…Moreover, live cell imaging analyses indicated that multinucleated giant cells resulted from a failure in cell division ( Fig. S2d and Supplementary Movie 4); as reported by others [51], mitotic abnormalities, chromosome mis-segregation, and aneuploidy were observed in transgenic mice expressing the human P301S FTLD-MAPT mutation.…”
Section: Tau Inclusions Accumulate On the Nuclear Envelopesupporting
confidence: 81%
“…Deutschl€ ander and colleagues cited an article demonstrating that MAPT mutations cause aneuploidy in neurons and glia, where the N279K MAPT mutation was analyzed but not reported in detail, as only aggregated data from different missense mutations are shown (5). Although aneuploidy can cause neurodegeneration, it can be linked to cancer in nonneural tissues (6).…”
mentioning
confidence: 99%
“…As summarized above, ploidy reduction/HST could either give rise to daughter cells with a diploid karyotype [37,42] or to daughter cell that are aneuploid and genomically unstable [7,36,39,[45][46][47][48], suggesting that this process might be differentially regulated in distinct cell types. Likewise, aneuploidy and genomic instability appear to be more tolerated in proliferating hepatocytes [36,39,40,[49][50][51], whereas in other cell types, aneuploidy and genomic instability are associated with cell death or senescence [117][118][119][120][121]. Again, it remains to be elucidated how these different cellular outcomes (tolerance/viability vs. apoptosis/senescence) are regulated in distinct cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cell fusion-derived aneuploidy and genomic instability are associated with impaired proliferation and overall decreased viability of cells. Several studies demonstrated that aneuploid cells were less proliferative [114,115], more apoptotic [116][117][118], or became senescent [119][120][121], which can most likely be attributed to impaired cellular homeostasis due to altered gene and protein expression levels (for review see [47]). Moreover, even in the context of "cell fusion in cancer", it has been shown that approximately 99% of tumor cell × normal cell hybrids have died or become senescent.…”
Section: What Is the Fate Of Cell Fusion-derived Aneuploid And Genomimentioning
confidence: 99%